Analytical solutions to boundary value problem of free vibration of sandwich thin circular plates with discrete elements - Żur, Krzysztof Kamil; Jaroszewicz, Jerzy; Dragun, Łukasz (Zielona Góra: Uniwersytet Zielonogórski)
In the paper the influence function and the method of partial discretization in free axisymmetric vibration analysis of multilayered circular plates of constant and linearly variable thickness were presented. The effects of shear deformation and rotary inertia for the core as well as the facings were neglected. An analytical investigation based on the classical plate theory was made for the multilayered plate which satisfies Sokołowski`s condition.
Keywords: free vibrations; sandwich circular plate; non-homogeneous material; variable parameters; annular mass